Locking Down Secure Open Source Software: Can even secure open source software ever be considered truly safe? - Savage, Neil (Communications of the ACM, 2023)
The article focuses on the security of open source software. The author discusses the discovered vulnerability within the string of code called "Log4J," examines the Social Cyber, Hybrid AI to Protect Integrity of OpenSource Code project being launched by the U.S. Defense Advanced Research Projects Agency (DARPA), and explores how social processes dangerously interact with code.